PEMBELAJARAN SOCCER LIKE GAMES DALAM MENINGKATKAN KETERAMPILAN DASAR SEPAKBOLA PADA SISWA DI SMPN 1 KARAWANG - Teten Hidayat (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2017)
The purpose of this study is to determine the influence of learning soccer like games to the basic skills of football. Physical education is an educational effort to develop all aspects of education not just about the activity of motion. Learning physical education in school in the form of physical activity and one of the materials taught the activities of the game and sports so that the learning process that takes the form of play activities. Experimental method aims to examine a problem to obtain a result. In addition, the authors want to know the effect of independent variables on the dependent variable investigated or observed is the influence of Learning of Soccer Like Games Football basic skills. The conclusion obtained is the learning soccer like games give a significant influence on the basic skills of football in students SMPN 1Karawang.